2008
DOI: 10.1016/j.biopsych.2008.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The Opioid Peptides Enkephalin and β-Endorphin in Alcohol Dependence

Abstract: Together these results indicate a contribution of beta-endorphin to ethanol consumption and dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
56
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 49 publications
11
56
0
1
Order By: Relevance
“…The POMC deficiency affects female mice more strongly than males, suggesting that POMC may influence alcohol consumption in a sex-specific manner [Zhou et al, JPET #245621R3 2017b]. Our result is in line with early studies demonstrating a decreased alcohol intake in betaendorphin and MOP-r knockout mice with more notable differences in females [Hall et al, 2001;Racz et al, 2008] (Table 2). Sex differences have also been observed in a human genetic study, showing that the Pomc two-marker haplotype is associated with alcoholism only in women [Racz et al, 2008].…”
Section: Pro-opiomelanocortin (Pomc)/β-endorphin and Mu-opioid Resupporting
confidence: 82%
See 3 more Smart Citations
“…The POMC deficiency affects female mice more strongly than males, suggesting that POMC may influence alcohol consumption in a sex-specific manner [Zhou et al, JPET #245621R3 2017b]. Our result is in line with early studies demonstrating a decreased alcohol intake in betaendorphin and MOP-r knockout mice with more notable differences in females [Hall et al, 2001;Racz et al, 2008] (Table 2). Sex differences have also been observed in a human genetic study, showing that the Pomc two-marker haplotype is associated with alcoholism only in women [Racz et al, 2008].…”
Section: Pro-opiomelanocortin (Pomc)/β-endorphin and Mu-opioid Resupporting
confidence: 82%
“…Our result is in line with early studies demonstrating a decreased alcohol intake in betaendorphin and MOP-r knockout mice with more notable differences in females [Hall et al, 2001;Racz et al, 2008] (Table 2). Sex differences have also been observed in a human genetic study, showing that the Pomc two-marker haplotype is associated with alcoholism only in women [Racz et al, 2008]. These results also contribute to the idea that there are sex differences in opioid regulation of alcohol dependence [Becker and Koob, 2016].…”
Section: Pro-opiomelanocortin (Pomc)/β-endorphin and Mu-opioid Resupporting
confidence: 82%
See 2 more Smart Citations
“…In the clinic, basal levels of plasma β-E, as well as a rise in this peptide following alcohol administration, correlate with a heritable risk for high consumption (Dai et al 2005;Kiefer et al 2006). Our laboratory and others have demonstrated that β-Edeficient mice exhibit altered patterns of EtOH consumption, which depend upon sex (Williams et al 2007;Zhou et al 2017), and a Pomc haplotype marker has been associated with human alcoholism in women, but not men (Racz et al 2008). However, the mechanisms responsible for this interaction remain unknown.…”
Section: Introductionmentioning
confidence: 99%